A microcontroller-based taste sensing system for the verification of Eurycoma longifolia - Rahman, A. S A; Yap, M. M S; Ali Yeon, Md Shakaff; Mohd Noor, Ahmad; Dahari, Z.; Zhari, Ismail; Muhammad Suzuri, Hitam (Elsevier, 2009)
Link to publisher's homepage at www.elsevier.com